Bimodal expressivity in dominant retinitis pigmentosa genetically linked to chromosome 19q. Issue 9 (September 1995) - Evans, K; al-Maghtheh, M; Fitzke, F W; Moore, A T; Jay, M; Inglehearn, C F; Arden, G B; Bird, A C
Abstract : A clinical, psychophysical, and electrophysiologic study was undertaken of two autosomal dominant retinitis pigmentosa pedigrees with a genetic mutation assigned to chromosome 19q by linkage analysis. Members with the abnormal haplotype were either symptomatic with adolescent onset nyctalopia, restricted visual fields, and non-detectable electroretinographic responses by 30 years of age, or asymptomatic with normal fundus appearance and minimal or no psychophysical or electroretinographic abnormalities. There was no correlation in the severity in parents and their offspring. Pedigree analysis suggested that although the offspring of parents with the genetic mutation were at 50% risk of having the genetic defect, the risk of being symptomatic during a working lifetime was only 31%. Such bimodal phenotypic expressivity in these particular pedigrees may be explained by a second, allelic genetic influence and may be a phenomenon unique to this genetic locus. Genetic counselling in families expressing this phenotype can only be based on haplotype analysis since clinical investigations, even in the most elderly, would not preclude the presence of the mutant gene.